Global trends and hotspots in research on extended reality in sports: A bibliometric analysis from 2000 to 2021 - Jie Zhao; Jie Mao; Jing Tan (Digital Health, 2022)
Objective Extended reality technologies (e.g. virtual reality (VR), augmented reality (AR) and mixed reality (MR)) are gaining popularity in sports owing to their unique advantages. This study aims to analyse the progress of the application of extended reality technology in sports and reveal its cooperative features, research hotspots and development trends. Methods We searched the literature in the Web of Science Core Collection (WoSCC) database within the period 2000 to 2021 and conducted a bibliometric analysis. The analysis methods included statistical, co-occurrence, hierarchical clustering and social network analyses. Results A total of 340 articles were gathered. The literature related to its research showed an increasing trend over time. The paper collaboration rate was 90.88% (309/340 papers), and the degree of author collaboration was 3.96 (1345/340). VR was found to be the most productive journal, and Queen's University Belfast was the most productive institution. The United States, China and the United Kingdom were the three main contributors to the field. The foundational themes in sports extended reality research were (i) sports games and extended reality systems, (ii) virtual simulation devices and artificial intelligence, (iii) sports training and performance and (iv) age-appropriate physical activity, sports rehabilitation and physical education. Conclusion The level of author collaboration was low, but the degree of author collaboration is largely on the rise. The closeness of the collaboration between institutions and countries was also low. In addition, the subject of sport extended reality is relatively fragmented. Therefore, more research is needed to strengthen it in the future.